Clinical and antimicrobial profile of Coagulase Negative staphylococci in a tertiary care hospital - Chavan, Sonal Prakash; Jalgaonkar, Suresh V.; Raut, Sharmila S.; Khadse, Ravindra K. (International Journal of Research in Medical Sciences, 2017)
Background: Coagulase negative staphylococci (CoNS) are gaining importance because of their role as pathogens in certain clinical conditions and their marked resistance to antibiotics. Their species distribution and slime production has important correlation with the antimicrobial susceptibility pattern. Aim of this study was to determine clinically significant CoNS, their species distribution, slime production and antimicrobial susceptibility pattern in a tertiary care hospital. Methods: Identification, speciation and antimicrobial sensitivity testing were performed using standard microbiological techniques. Slime production was also tested by microtiter plate. Antimicrobial susceptibility testing was performed by modified Kirby Bauer method as per the CLSI guidelines. Results: A total 204 (49.88%) CoNS were found to be clinically significant. Percentage of clinical significance was high in urine isolates (88.88%) followed by pus (47.78%) and blood (45.56%). The most common CoNS infection was septicaemia (54.9%) followed by abscesses and wound infections (26.5%) and urinary tract infection (15.8%). S. epidermidis (46.1%) was the commonest species in CoNS infection followed by S. haemolyticus (22.1%), S. lugdunensis (11.8%) and S. saprophyticus (8.3%). Slime production was seen in 56.4% isolates by microtiter plate method. Maximum resistance was seen to penicillin (92.25%), followed by cotrimoxazole (73.03%), norfloxacin (73.03%), tetracycline (71.07%), gentamicin (69.6%) and cefoxitin (63.2%). Conclusions: The role of CoNS as pathogen, particularly nosocomial and opportunistic is increasing. Identification of species, slime production and antimicrobial susceptibility of CoNS is highly desirable to permit a more precise determination of host-pathogen relationship and knowledge of pathogenicity.